Pediatric rhabdomyosarcoma with bone marrow metastasis. Issue 5 (26th February 2020) - Bailey, Kayleen A.; Wexler, Leonard H.
Abstract: Background: Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma of adolescence and childhood. Although most patients with localized RMS are cured, outcome of those with metastatic disease remains unsatisfactory. RMS with bone marrow (BM) metastasis accounts for approximately 6% of all cases with RMS and has a 3‐year event‐free survival of 14%. Our study aims to describe our institution's experience of patients with metastatic RMS with BM involvement. Methods: This was a single‐institution retrospective study from Memorial Sloan Kettering Kids, a tertiary pediatric oncology center. Patients with RMS who were diagnosed with BM metastasis between 1998 and 2018 were identified from pathology reports. Results: For patients with RMS and BM positivity at diagnosis ( N  = 27), the median survival was 1.5 years. The 1‐, 2‐, and 3‐year overall survival (OS) were 81%, 32%, and 20%, respectively. There is one long‐term (defined as >4 year) survivor who is still alive 14.9 years after diagnosis despite two metastatic recurrences. An Oberlin status of 4 that included BM metastasis portended a 3‐year OS of 0%. Conclusions: Although most patients will respond to initial therapy, BM metastasis at the time of diagnosis lends a near‐fatal diagnosis in pediatric patients with RMS. Novel therapies are desperately needed to consolidate their initial remission.